The role of the international criminal court in global justice - Afyare, Abdifatah Ahmed Ali (International Journal of Innovative Research and Scientific Studies, 2025)
This investigates the effectiveness of the International Criminal Court (ICC) in achieving global justice, focusing on the critical question of whether the ICC’s mechanisms for prosecuting war crimes and crimes against humanity effectively deter future atrocities and promote accountability. Through qualitative analysis of case studies involving ICC interventions and quantitative assessment of crime incidence before and after ICC involvement, the research finds that while the ICC has made strides in international law enforcement, its deterrent effect remains limited and varies considerably based on contextual factors such as state cooperation and political will. Notably, data indicates a correlation between ICC interventions and a temporary reduction in atrocity crimes in specific regions, suggesting the potential for the ICC to influence global norms surrounding accountability. The significance of these findings extends beyond legal frameworks, as they underscore the ICC’s role in shaping a collective responsibility toward human rights and global health by providing a legal basis for accountability that is essential for peace and stability. Furthermore, the study’s implications may inform healthcare strategies in post-conflict societies, where establishing the rule of law and addressing past injustices can have profound effects on community health and resilience. Ultimately, this research contributes to the broader discourse on international justice, highlighting the need for strengthening the ICC’s mechanisms and increasing global collaboration to enhance its impact on preventing atrocities and fostering sustainable peace.